Utilization of indigenous design on modern contemporary applications to help promote and strengthen national / cultural identity to Filipinos ages 8-18 - Renacido, Mark Jay B. (College of Fine Arts, University of the Philippines Diliman, 2016)
There is a vast collection of indigenous designs in the Philippines ranging from the tapestries of the Maranao to the embroideries of the Bagobo. However, globalization has altered people's perception of value and beauty. The Filipinos' judgments are affected by Western culture resulting to the distortion of Filipinos' sense of cultural identity. Filipinos especially the youth lack information about our own distinct culture, resulting to being ashamed of our indigenous culture because thinking that it is inferior compared to foreign cultures. Promoting indigenous designs in the Philippines through its utilization on modern contemporary applications creates a strong sense of character and a boost in self-esteem and pride as a Filipino. As Dr. Peralta explains in Philippine Ethnic Patterns, to better understand the indigenous mind, there is a need to articulate how unitary elements are isolated. Instead of beginning with a mix of design patters and single elements, focus probably should made to traditional ideogenesis or the generation of concepts by indigenous groups.